Management of the Implementation of the Talaqqi Method and Its Effectiveness in the Qur’an Memorization (Tahfidz) Program at Pondok Pesantren Darussalamah Al Mubarok Cianjur - Permana, Diansyah; Gandara, Tedi; Khadafi, Ahmad; Jefri, Muhammad; Al-Maky, M. Jamhar (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2026)
This study examines the management of implementing the Talaqqi method and its effectiveness in the Tahfidz Al-Qur’an program at Darussalamah Al Mubarok Islamic Boarding School, Cianjur. The research aims to analyze how planning, organizing, implementing, and evaluating the Talaqqi method contribute to improving students’ memorization quality. Using a qualitative field-study approach, data were obtained through interviews, observations, and documentation involving tahfidz supervisors and students. The findings reveal that the management of Talaqqi implementation is carried out systematically through structured scheduling, grouping based on ability levels, and regular evaluation of memorization progress. The method proved effective in strengthening students’ mastery of tajweed, fluency, and discipline due to intensive face-to-face interaction between teacher and student. However, challenges remain, including limited teacher-student ratio, varied memorization abilities, and time constraints. Strengthening human resources, optimizing group management, and improving review schedules are essential to enhance the sustainability and effectiveness of the program.